2020
DOI: 10.1186/s41935-020-00183-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of Cameriere’s Indian-specific formula for age estimation on right and left sides of orthopantomogram

Abstract: Background: Age estimation is of prime importance in forensic science and clinical dentistry. In children, age estimation can be done by skeletal maturity indicators like hand-wrist radiographs and dental age estimation. Skeletal maturity indicators compared with dental age estimation is limited as they are influenced by various environmental parameters, whereas calcification of teeth depends on genes rather than environmental factors. Many of the dental age estimation methods use extracted teeth, which are qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This outcome indicates that mandible ramus exhibits better sexual dimorphism. In 2020, Poornima Vadla et al [ 17 ] introduced a technique based on permanent mandible teeth of the left-sided jaw. Their study focused on estimating age with high accuracy based on the Camerier method applied from an Indian-specific formula on the left and right sides of mandibular teeth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This outcome indicates that mandible ramus exhibits better sexual dimorphism. In 2020, Poornima Vadla et al [ 17 ] introduced a technique based on permanent mandible teeth of the left-sided jaw. Their study focused on estimating age with high accuracy based on the Camerier method applied from an Indian-specific formula on the left and right sides of mandibular teeth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study utilized the left quadrant as no statistical difference between growth rate of dentition on right and side was documented in the literature [ 39 ]. Furthermore, Vadla et al [ 2 ] concluded that the left side of panoramic radiographs showed “superior results” in comparison to the left side. Dental age was then estimated by employing Cameriere’s (Italian) linear Regression Formula [ 8 ]: Age = 8.971 + 0.375g + 1.631(x 5 ) + 0.674 (N 0 ) − 1.…”
Section: Methodsmentioning
confidence: 99%
“…The estimation of an individual’s age is a fundamental component of forensic odontology, which is a branch of dentistry that examines dental evidence [ 1 , 2 ]. The demand for accurate age estimation is imperative for issues pertaining to illegal immigration (child labour), legal medicine (human trafficking/kidnapping), orthodontic treatment, criminal cases, adoption of individuals without birth certification and natural or mass disasters [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various types of CNN are GoogLeNet [9], DenseNet [13], and ResNets are implemented. The proposed work uses ResNets [22] in DCNN. Human age is determined by facial structure [14,29] and it may be different from that detected using our human eye.…”
Section: F1-scorementioning
confidence: 99%